Comparison of the Indonesian Military Legal System with the Malaysian Military Legal System - Anis Fauzan; Walidul Halim; Irwan Triadi (Journal of Law Perspectives Review, 2026)
This study addresses the problem of how differences in legal traditions influence the structure and enforcement of military law in Indonesia and Malaysia. It aims to examine and compare the legal foundations, institutional structures of military courts, and the characteristics of law enforcement applied to members of the armed forces in both countries. The research employs a normative juridical method with a comparative law approach by analyzing statutory regulations, particularly Law Number 31 of 1997 on Military Courts in Indonesia and the Armed Forces Act 1972 (Act 77) in Malaysia, as well as relevant legal literature and doctrines. The findings reveal that the principal differences between the two systems derive from their respective legal traditions—Civil Law in Indonesia and Common Law in Malaysia—which shape the organization of military courts, jurisdictional design, and procedural mechanisms for adjudicating military offenses. Indonesia relies on a codified and hierarchical military judicial structure, whereas Malaysia integrates common law principles within its court-martial system. Nevertheless, both systems share a fundamental objective, namely maintaining discipline, hierarchy, and command effectiveness within military institutions. In conclusion, despite structural and procedural distinctions, the military legal systems of Indonesia and Malaysia pursue similar normative goals. This study contributes to the development of comparative military law and offers a reference for strengthening military legal reform in Indonesia in alignment with the principles of the rule of law, military professionalism, and legal supremacy.